Enforcing transnational non-conviction-based confiscation orders: comparing the United Nations, European Union, Australian, and Indonesian legal frameworks - Dion Valerian (Komisi Pemberantasan Korupsi, 2025)
The present article compares and critically examines the enforcement of transnational non-conviction-based confiscation (NCBC) orders in the United Nations (UN), European Union (EU), Australian, and Indonesian legal frameworks utilising comparative legal and document analyses. The results serve as a reference for regulating a fair and effective framework for transnational NCBC enforcement in Indonesian law. This research compares the nature of NCBC, adaptive response conceptualisation, mechanisms facilitating transnational NCBC enforcement, and procedural safeguards in the transnational enforcement stage. It concludes that the relevant UN, EU, and Australian legal frameworks can serve as benchmarks for transnational NCBC enforcement in Indonesia, specifically regarding norm formulation of NCBC, international cooperation for effecting transnational NCBC orders, and the corresponding procedural safeguards to ensure fairness. However, the research findings indicate that practices of transnational NCBC enforcement in these jurisdictions have yet to generate significant references for empirical effectiveness benchmarking. Furthermore, this article discovers crucial implications for the criminological theory of adaptive response. Lastly, reconceptualisation of the Indonesian NCBC regime and proposals for reforming the Criminal Assets Confiscation Bill and the Mutual Legal Assistance in Criminal Matters Act are recommended.